Advances in Management and Applied Economics 2021
DOI: 10.47260/amae/1114
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Liquidity on Profitability: A Study on the Commercial Banks in Bangladesh

Abstract: This research aims to investigate the effect of banks' liquidity on its profitability; with the ordinary course of business and in the medium term (10 years). A quantitative analysis is performed on a statistical sample of forty (40) commercial banks in Bangladesh. Secondary data is used to evaluate the performance of the last ten years (2009-2018) of the annual report of the commercial banks in Bangladesh with 206 bank years of data gathered to consider all Bangladeshi commercial banks. Proposed variables are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 0 publications
0
12
0
1
Order By: Relevance
“…If a company determines large assets, it is likely that what will occur at the level of liquidity will be safe, but the expectation of getting large profits will decrease which will then have an impact on company profitability or vice versa. In Paul et al, (2021), he also argues that it strengthens that liquidity has a significant effect on profitability.…”
Section: Figure 1 Construction and Property Sector Performancementioning
confidence: 96%
See 1 more Smart Citation
“…If a company determines large assets, it is likely that what will occur at the level of liquidity will be safe, but the expectation of getting large profits will decrease which will then have an impact on company profitability or vice versa. In Paul et al, (2021), he also argues that it strengthens that liquidity has a significant effect on profitability.…”
Section: Figure 1 Construction and Property Sector Performancementioning
confidence: 96%
“…Based on previous research studies and gap analysis of research Arista & Topowijono (2017), Paul et al, (2021), Sari (2019) and Rohmah (2020), so it is interesting to carry out further research to analyze the profitability of the property sector. In this study, it will be investigated…”
Section: Figure 1 Construction and Property Sector Performancementioning
confidence: 99%
“…Ibrahim and Aqeel (2017) suggested an optimum utilization of available liquidity for the purpose of increasing bank's profitability and also gave recommendation to the banks for adopting a perfect framework of liquidity management for assuring sufficient liquidity (Ibrahim & Aqeel, 2017). Paul, Bhowmik, and Famanna (2021) aims to examine the impact of liquidity on commercial bank's profitability for the year 2009-2018 in Bangladesh. A sample of forty commercial banks was collected for their study and the data were collected from the annual reports of that selected banks.…”
Section: General Considerationmentioning
confidence: 99%
“…The explanatory variables are as deposit to asset ratio, cash equivalent to deposit ratio, loan to deposit ratio, current ratio, and the liquidity assets ratio. By applying the multiple regression models their study found out that there is a positive and significant relationship between liquidity and profitability of commercial banks in Bangladesh (Paul et al, 2021). Charmler, Musah, Akomeah, and Gakpetor (2018) claimed that liquidity is positively associated with return on assets (ROA) as well as there is a weak positive relation between the ratios of liquid assets to total assets regarding return on equity (ROE).…”
Section: General Considerationmentioning
confidence: 99%
“…The results suggested that if the firm can manage the working capital in cash, accounts receivable, and inventories properly, it will ultimately increase the profit. Paul, Bhowmik, and Famanna (2020) examined the impact of Liquidity and Profitability on the Commercial Banks in Bangladesh. Liquidity is used as an independent variable, and profitability is used as a dependent variable loan to deposit ratio, deposit assets ratio, call deposit receipt, and loan to asset ratio.…”
Section: A Peer-reviewed Journal Of Management and Economicsmentioning
confidence: 99%